MATTERHORN: phase III study of durvalumab plus FLOT chemotherapy in resectable gastric/gastroesophageal junction cancer - Janjigian, Yelena Y; Van Cutsem, Eric; Muro, Kei; Wainberg, Zev; Al-Batran, Salah-Eddin; Hyung, Woo Jin; Molena, Daniela; Marcovitz, Michelle; Ruscica, Dario; Robbins, Scott H; Negro, Alejandra; Tabernero, Josep (Future oncology (London, England), 2022)
Standard-of-care for resectable gastric/gastroesophageal junction cancer includes surgery and neoadjuvant-adjuvant 5-fluorouracil-leucovorin-oxaliplatin-docetaxel (FLOT) chemotherapy. Early-phase clinical studies support further clinical development of the immune checkpoint inhibitor (ICI); durvalumab, an anti-PD-L1 antibody, in patients with gastric/gastroesophageal junction cancer. Accumulating evidence indicates that ICIs combined with FLOT chemotherapy improve clinical outcomes in patients with advanced or metastatic cancer. We describe the rationale for and the design of MATTERHORN, a randomized, double-blind, placebo-controlled, phase III study investigating the efficacy and safety of neoadjuvant-adjuvant durvalumab and FLOT chemotherapy followed by adjuvant durvalumab monotherapy in patients with resectable gastric/gastroesophageal junction cancer. The planned sample size is 900 patients, the primary end point is event-free survival and safety and tolerability will be evaluated. Clinical trial registration: NCT04592913 (ClinicalTrials.gov).